2008
DOI: 10.1530/eje-08-0410
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD40 and thyroglobulin genes with later-onset Graves' disease in Taiwanese patients

Abstract: Objective: Graves' disease (GD) is known to be associated with thyroglobulin (TG) and CD40 genes. Therefore, we decided to investigate the relationship of age at onset of GD with CD40 and TG gene susceptibilities in a Taiwanese population. Design and method: We analyzed the association of TG and CD40 polymorphisms with age at onset of GD in Taiwanese patients. We stratified patients into those with early onset (!40 years; 30.3G4.8 years; nZ135) and later onset (R40 years; 52.3G6.3 years; nZ80) and compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Indeed the T allele and TT genotype were found to carry a protective effect and even linked to later-age onset of GD. [60, 61]. In animal models of GD, blockade of CD40 stimulation has suppressed the progression to murine thyroiditis [53, 62, 63].…”
Section: Genetic Disruption Of Co-stimulation – Cd40 and Ctla-4 Genesmentioning
confidence: 99%
“…Indeed the T allele and TT genotype were found to carry a protective effect and even linked to later-age onset of GD. [60, 61]. In animal models of GD, blockade of CD40 stimulation has suppressed the progression to murine thyroiditis [53, 62, 63].…”
Section: Genetic Disruption Of Co-stimulation – Cd40 and Ctla-4 Genesmentioning
confidence: 99%
“…There are several polymorphisms distributed throughout the TG gene. Some of them have been associated with AITD [32][33][34][35][36][37][38][39] and experimental autoimmune thyroiditis in different strains of mice [35].…”
Section: Introductionmentioning
confidence: 99%
“…CHRNA9 encodes nicotinic acetylcholine receptor alpha 9 (nAChRα9) and is expressed among others in mice B lymphocytes subtypes but its function is not clearly understood (12). It has been shown that nAChR α9α10 are coupled to CD40 (12) encoded by a gene previously implicated as a susceptibility locus to GD (13)(14)(15)(16)(17)(18). While CHRNA9 can potentially be involved in GD pathogenesis, on the basis of the positional mapping data as well as the relatively high expression in CD4 and CD8 T cells Chan et al tentatively proposed GDCG4p14 as a the primary diseases-associated locus (2).…”
Section: Q27 (Rs9355610)mentioning
confidence: 99%